Combined Phacoemulsification With Goniosynechialysis Under Ophthalmic Endoscope for Primary Angle-closure Glaucoma After Failed Trabeculectomy. Issue 10 (October 2020) - Nie, Li; Fu, Lin; Chan, Yau Kei; Fang, Aiwu; Pan, Weihua
Abstract : Precis: Phacoemulsification with goniosynechialysis under an ophthalmic endoscope (Phaco-OE-GSL) is safe and able to lowering intraocular pressure (IOP) for failed trabeculectomy in primary angle-closure glaucoma with cataract. The larger pupil diameter and younger age are identified as the 2 risk factors for surgical outcome. Purpose: To investigate the efficacy and safety of combined Phaco-OE-GSL for primary angle-closure glaucoma with cataract after failed trabeculectomy. Materials and Methods: Twenty-five patients (25 eyes) were enrolled in this retrospective study. IOP, best-corrected visual acuity, and number of glaucoma medications at baseline and each postoperative follow-up visit were recorded. Peripheral anterior synechia (PAS) was recorded using gonioscopy. Binary logistic regression was used to analyze the risk factors of surgical failure. Results: The mean follow-up duration was 17.9±11.4 months. The mean IOP was significantly lower than the preoperative baseline IOP at all time points ( P <0.001). The mean IOP was reduced from 24.4±6.5 mm Hg at baseline to 14.2±3.0 mm Hg at the last follow-up. The mean preoperative number of glaucoma medications was 2.2±1.2, which reduced to 0.9±1.1 at the last follow-up. The complete success rates at 1 year and the last follow-up were 70.6% and 68%, respectively. The total success rates were 96% and 92%, respectively. The most common postoperative complications were IOP spikes (48%) and hyphemas (32%). All eyes had degrees of PAS recurrence, with a range of 96.1±52.5 degrees (30 to 210 degrees) after 4 to 6 months. Larger pupil diameter and younger age were significantly associated with the failure of Phaco-OE-GSL. Conclusions: Phaco-OE-GSL is safe and can lower IOP for failed trabeculectomy in PACG with cataract despite the high recurrence rate of PAS.